Estudo químico do fungo Memnoniella levispora : busca por metabólitos secundários inibidores da Phytophtora nicotianae - Ribeiro, Alany Ingrid (2015)
Among the various diseases which attack citrus worldwide, the gummosis is caused by species of the genus Phytophthora. The various species present in the literature, the most severe in Brazil is P. nicotianae. This pathogen produces resistance’s structures in the soil, thus the best control method is the exclusion. There are other ways to preventive, as is the case of the use of synthetic fungicides which help in the combat, however , the widespread use thereof, can favor the emergence of resistant strains to the active ingredient , as well as being damaging to the environment. In this context, one of saprobes fungi (Memnoniella levispora) found in the Brazilian semi -arid region, has received special attention as a biological control agent that proves to be an alternative and effective method. Thus, the objective of this study was to evaluate the effect of the growth of this fungus in solid and liquid, through five different culture media (PD, PDY, PDM, CZA, CC), perform isolation and identification of metabolites from the most suitable means and then submit them to the mycelial growth tests of the P. nicotianae. After a comparative by HPLC-DAD, HPLC-UV and NMR of this media, the CC proved to be the most productive. For showing good results this medium was reproduced on a large scale in liquid medium. After partitioning and fragmentation of the material, the extracts were analyzed and biologically tested against mycelial growth of P. nicotianae, in order to realize a biomonitored study. The fraction of ethyl acetate liquid of the carrot and corn medium, was considerably inhibited the pathogen growth. Therefore, by the technique LC-SPE-NMR along with the other techniques mentioned, it was possible to identify and isolate eight structures of this fraction, which griseofulvina and analogues, 3 of which purports to be unpublished yet. The Griseofulvin was tested and showed about 72% of the inhibition of mycelial growth of Phythophtora, which leads us to research on the antifungal activity of this and other secondary metabolites in the fight against P. nicotianae and other pathogens.